Improving Care Transitions: The Patient Perspective - Cawthon, Courtney (2012)
After hospital discharge, patients commonly suffer potentially avoidable adverse events and hospital readmissions. As hospitals implement interventions to improve discharge transitions, it is important to understand patients’ perspectives on which intervention components are most beneficial. We examined a sample of 125 patients randomized to the intervention arm of the Pharmacist Intervention for Low Literacy in Cardiovascular Disease (PILL-CVD) study who completed a telephone survey about the helpfulness of different components of the PILL-CVD intervention, which included medication reconciliation, inpatient counseling, simple adherence aids, and telephone follow-up. The majority of patients indicated it was “very helpful” to speak with a pharmacist about their medications before discharge (72.8%), particularly about how to take the medications, and how to prevent and manage side effects. Receiving an illustrated medication list (69.6%) and follow-up phone call after discharge (68.0%) were also considered very helpful. Patients with limited health literacy indicated the greatest benefit. Patients also reported feeling more comfortable speaking with their outpatient providers about their medications after receiving the intervention. In conclusion, patients – particularly those with limited health literacy – found a hospital pharmacist-based intervention to be very helpful and empowering.